Endothelial Notch1 signaling in white adipose tissue promotes cancer cachexia - Taylor, Jacqueline; Uhl, Leonie; Moll, Iris; Hasan, Sana Safatul; Wiedmann, Lena; Morgenstern, Jakob; Giaimo, Benedetto Daniele; Friedrich, Tobias; Alsina Sanchis, Elisenda; De Angelis Rigotti, Francesca; Mülfarth, Ronja; Kaltenbach, Sarah; et al. (Nature cancer, 2023)
Cachexia is a major cause of morbidity and mortality in individuals with cancer and is characterized by weight loss due to adipose and muscle tissue wasting. Hallmarks of white adipose tissue (WAT) remodeling, which often precedes weight loss, are impaired lipid storage, inflammation and eventually fibrosis. Tissue wasting occurs in response to tumor-secreted factors. Considering that the continuous endothelium in WAT is the first line of contact with circulating factors, we postulated whether the endothelium itself may orchestrate tissue remodeling. Here, we show using human and mouse cancer models that during precachexia, tumors overactivate Notch1 signaling in distant WAT endothelium. Sustained endothelial Notch1 signaling induces a WAT wasting phenotype in male mice through excessive retinoic acid production. Pharmacological blockade of retinoic acid signaling was sufficient to inhibit WAT wasting in a mouse cancer cachexia model. This demonstrates that cancer manipulates the endothelium at distant sites to mediate WAT wasting by altering angiocrine signals.
Insgesamt 38 Seiten (S. 1544-1560, 15 ungezählte Seiten, S. 1-6)
Online veröffentlicht: 25. September 2023
Gesehen am 08.12.2023